Comparing macroecological patterns across continents: evolution of climatic niche breadth in varanid lizards. Issue 8 (26th September 2016) - Lin, Long‐Hui; Wiens, John J.
Abstract : Macroecological analyses often test hypotheses at the global scale, or among more closely related species in a single region (e.g. continent). Here, we test several hypotheses about climatic niche widths among relatively closely related species that occur across multiple continents, and compare patterns within and across continents to see if they differ. We focus on the lizard genus Varanus (monitor lizards), which occurs in diverse environments in Africa, Asia, and Australia. We address three main questions. 1) How do climatic niche breadths of species on a given niche axis change based on the position of species along that niche axis? (E.g. are species that occur in more extreme environments more narrowly specialized for those conditions?) 2) Are there trade‐offs in niche breadths on temperature and precipitation axes among species, or are niche widths on different axes positively related? 3) Is variation in niche breadths among species explained primarily by within‐locality seasonal variation, or by differences in climatic conditions among localities across the species range? We generate a new time‐calibrated phylogeny for Varanus and test these hypotheses within and between continents using climatic data and phylogenetic methods. Our results show that patterns on each continent often parallel each other and global patterns. However, in many other cases, the strength of relationships can change dramatically among closely related species on different continents. Overall, we found that: 1) species in warmer environments have narrower temperature niche breadths, but there is no relationship between precipitation niche breadth and niche position; 2) temperature and precipitation niche breadths tend to be positively related among species, rather than showing trade‐offs; and 3) within‐locality seasonal variation explains most variation in climatic niche breadths. Some of these results are concordant with previous studies (in amphibians and North American lizards), and might represent general macroecological patterns.